Lecturer tracking system using bluetooth mobile phone / Syed Ridzuan Syed Nopal - Syed Nopal, Syed Ridzuan (Faculty of Information Technology and Quantitative Sciences, 2004)
This project will focus on developing of the lecturer tracking system using Bluetooth mobile phone. The system will manipulate a Symbian 60 OS at mobile phone a Bluetooth connection to send a lecturer identification number to the computer. Even though the text file can be send by mobile phone via Bluetooth but this method is inappropriate because the output cannot be directly in form of clear text. The study of telecommunication is an interesting filed because it involves digital signal processing, signal and systems, programming and more. This inspires people to improvise the technology into daily use. In this project, the technology of telecommunication, to be specific; Bluetooth, is integrated of improvised to the Symbian OS technology in Nokia mobile phone. Instead of human to human telecommunication, this system creates a new entity which is machine to human telecommunication.